2020
DOI: 10.1111/jdv.16849
|View full text |Cite
|
Sign up to set email alerts
|

The evolving field of Dermato‐oncology and the role of dermatologists: Position Paper of the EADO, EADV and Task Forces, EDF, IDS, EBDV–UEMS and EORTC Cutaneous Lymphoma Task Force

Abstract: Background The incidence of skin cancers has been increasing steadily over the last decades. Although there have been significant breakthroughs in the management of skin cancers with the introduction of novel diagnostic tools and innovative therapies, skin cancer mortality, morbidity and costs heavily burden the society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 107 publications
0
25
0
Order By: Relevance
“…The strength of this study lies in its unique approach and design as until to date no standard test method has been developed to assess other PA than the three mandatory efficacy statements. To our knowledge, this study has identified for the first time a specific test-battery for objectifying the suitability of appropriate sunscreen formulations and thus provided a significant impetus for the current scientific and political focus on improvement of occupational health in highly UVR-exposed OW [ 50 – 52 ]. Our study aims to open up a discussion on new testing methods focusing on outdoor workers’ expectations and the intended scope of application that complement the so far mandatory labels and assist in making informed, evidence-based decisions when choosing an appropriate sunscreen product.…”
Section: Discussionmentioning
confidence: 99%
“…The strength of this study lies in its unique approach and design as until to date no standard test method has been developed to assess other PA than the three mandatory efficacy statements. To our knowledge, this study has identified for the first time a specific test-battery for objectifying the suitability of appropriate sunscreen formulations and thus provided a significant impetus for the current scientific and political focus on improvement of occupational health in highly UVR-exposed OW [ 50 – 52 ]. Our study aims to open up a discussion on new testing methods focusing on outdoor workers’ expectations and the intended scope of application that complement the so far mandatory labels and assist in making informed, evidence-based decisions when choosing an appropriate sunscreen product.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in life expectancy and population ageing along with the introduction of in vivo diagnostic tools (e.g. dermoscopy) and new treatments for advanced melanoma and KCs have resulted in unprecedented changes in the organization of patient care in the clinical setting [ 7 ]. This generates a great burden on national healthcare systems and economies.…”
Section: Introductionmentioning
confidence: 99%
“…Secondary prevention encompasses the various strategies of early detection of skin tumors, including skin cancer screening programs. These strategies are expected to reduce the epidemiologic burden and the cost of skin cancer management–under the premise that skin cancer can be more easily and effectively treated at an early phase of development [ 7 ]. Dermatologists are the best trained and equipped specialists to provide early detection, but their success depends on patients receiving timely access to their services.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that it comprises a group of preventable diseases with known risk factors [ 9 ], a 45-fold increase of melanoma (and 80-fold of non-melanoma skin cancers) is expected over 8 decades. Australia is probably the only country that has managed to change this negative trend of melanoma incidence [ 14 ].…”
mentioning
confidence: 99%